2019
DOI: 10.1136/jech-2019-212674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise referral schemes upon health and well-being: initial observational insights using individual patient data meta-analysis from the National Referral Database

Abstract: ObjectivesTo examine if exercise referral schemes (ERSs) are associated with meaningful changes in health and well-being in a large cohort of individuals throughout England, Scotland, and Wales from the National Referral Database.MethodsData were obtained from 23 731 participants from 13 different ERSs lasting 6 weeks to 3 months. Changes from pre- to post-ERS in health and well-being outcomes were examined including body mass index (BMI), blood pressure (systolic (SBP) and diastolic (DBP)), resting heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 59 publications
2
29
1
Order By: Relevance
“…Previous evidence on primary care PA programs’ impact on HRQoL is mixed. Although some studies have found positive impact [ 12 , 16 , 20 , 37 , 42 44 ], our findings are in conflict with other studies showing minimal effects [ 19 , 45 48 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous evidence on primary care PA programs’ impact on HRQoL is mixed. Although some studies have found positive impact [ 12 , 16 , 20 , 37 , 42 44 ], our findings are in conflict with other studies showing minimal effects [ 19 , 45 48 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The number of existing ERS is thought to be in excess of 600 schemes in the UK. However, evidence concerning their effectiveness remains mixed [7]. A recent review [8] including six Randomised Controlled Trials (RCTs) noted positive impacts among patients referred for cardiovascular or mental health reasons, yet a lack of evidence for musculoskeletal referrals.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that the post-intervention magnitude of change observed in mental well-being for Co-PARS (5) was larger than that observed in a meta-analysis encompassing >23 000 participants across 13 different ERSs (3), which were comparable in nature to the usual care ERS in this study. 49 From the 6-month data, it appeared the scheme was not effective at promoting sustained PA behaviour change or mental well-being improvements. It must be noted, however, that the well-being levels were still higher than baseline and even small magnitudes of change (1-3) may be meaningful in clinical populations.…”
Section: Discussionmentioning
confidence: 98%